Four Undescribed Pyranones from the Scutellaria formosana-Derived Endophytic Fungi Ascomycota sp. FAE17 - Jianni Yang; Yang Hui; Zhaoxia Chen; Guangying Chen; Xiaoping Song; Zhenfan Sun; Changri Han; Wenhao Chen (Molecules, 2023)
Four undescribed pyranone derivatives, named ascomycopyrones A–D (1–4), as well as one known analogue simplicilopyrone (5) (this is the first study to report the absolute configuration), were isolated from the endophytic fungus Ascomycota sp. FAE17 derived from the flowers of Scutellaria formosa. The structures of these pyranones were identified by comprehensive spectroscopic and MS analyses, and the absolute configurations were determined by their experimental and quantum chemical electronic circular dichroism (ECD) calculations. All isolated compounds were tested for various bioactivities, including antibacterial, cytotoxic activity, and NO inhibitory activity. Unfortunately, none of the compounds showed significant bioactivities.